(untitled) (ASEAN Engineering Journal, 2012)
This paper looks at the nucleation stage, which is a fundamental stage of the granulation process. In order to clarify this mechanism the penetration time of the liquid into the powder bed was studied in both the cases of static and moving beds. Then the formation of the nuclei was studied by slowing down the binder addition rate. The effect of binder addition rate and viscosity on the size and binder fraction of the nuclei and granules was also demonstrated in this study. It was revealed that the penetration time is second power of drop size. Linear relationships between nucleus size and drop size onto both a static powder bed and a moving bed have also been found. It was shown the significant effect of the viscosity of binder on the drop sizes in both static and moving bed cases and granules keep their integrity; large nuclei produce large granules.